Accounting for people who think they hate accounting - Singal, Anurag., (Financial accounting and auditing collection., 2016)
The book Accounting for People Who Think They Hate Accounting is inspired by my IIM Ahmedabad days when grappling with accountancy suddenly becomes the "numero uno" priority of MBA Semester-1. Financial statements serve as a report card for a business through which managers and entrepreneurs can know their exact financial positions. These financial statements are prepared only through financial accounting. The main purpose of financial accounting is to help entrepreneurs exercise control over their business activities by controlling total costs incurred so that they are able to earn higher profits. So, in order to understand where exactly the business stands financially, knowledge of financial accounting is imperative. What is financial accounting? Why do I need to understand it? How will it help me in my business? Why is it important to me? Or Is it important to me? These are some of the questions that surface in the minds of young and aspiring entrepreneurs when they start their business or are on the verge of starting one. This book aims to answer them in the most practical and comprehensible manner possible so that accounting is no longer a nightmare for them.